Legal Politics the Position of Witnesses and the Right to Assitance by Advocates in Criminal Cases - RR Duni Nurbayanti; Agus Surono; Arti Panday (Journal Evidence Of Law, 2025)
The examination of witnesses is very important in the examination of criminal cases, because these witnesses can shed light on a case. A witness is an individual who has direct information about a criminal event. A person is brought forward as a witness because he immediately "hears, sees and experiences" the criminal case. Witnesses are expected to provide information for the purposes of investigation, prosecution, and justice about a criminal case. So important is the position of the witness, so the existence of the witness should be regulated in laws and regulations, including the assistance of advocates when giving information in front of police investigators. This study examines the legal politics of witness regulation in criminal cases, with reference to the Criminal Code. The Indonesian people are waiting for the renewal of the Criminal Code to replace Law Number 8 of 1981 concerning the Criminal Procedure Law. This research concludes that legal politics as shown by the Draft Criminal Procedure Law provides more opportunities for advocates to provide legal services for suspects and witnesses in the examination of criminal cases ranging from the level of investigation in the police to the examination in court